Herbicides and herbivory interact to drive plant community and crop‐tree establishment. Issue 8 (24th September 2018) - Stokely, Thomas D.; Verschuyl, Jake; Hagar, Joan C.; Betts, Matthew G.
Abstract: Land management practices often directly alter vegetation structure and composition, but the degree to which ecological processes such as herbivory interact with management to influence biodiversity is less well understood. We hypothesized that large herbivores compound the effects of intensive forest management on early seral plant communities and plantation establishment (i.e., tree survival and growth), and the degree of such effects is dependent on the intensity of management practices. We established 225‐m 2 wild‐ungulate (deer and elk) exclosures, nested within a manipulated gradient of management intensity (no‐herbicide control, light herbicide, moderate herbicide, and intensive herbicide treatments), replicated at the scale of whole harvest units (10–19 ha). Vegetation structure, composition, and crop‐tree responses to herbivory varied across the gradient of herbicide application during the first two years of stand establishment, with herbivory effects most evident at light and moderate herbicide treatments. In the moderate herbicide treatment, which approximates management applied to >2.5 million hectares in the Pacific Northwest, United States, foraging by deer and elk resulted in simplified, low‐cover plant communities more closely resembling the intensive herbicide treatment. Herbivory further suppressed the growth of competing vegetation in the light herbicide treatment, improving crop‐tree survival, and providing early evidence of an ecosystem service. By changing community composition and vegetation structure, intensive forest management alters foraging selectivity and subsequent plant–herbivore interactions; initial shifts in early seral communities are likely to influence understory plant communities and tree growth in later stages of forest development.